Types of Adjacency Pairs on The Six Minutes English Program in BBC Learning English - Wice Marsella; Azwandi Azwandi; Arasuli Arasuli (Journal of English Education and Teaching, 2023)
This research aimed to describe the Adjacency Pairs phenomena in the BBC Learning English, comprising two adjacency pairs aspects: The most frequently types of adjacency pairs used by the participants and the most frequently initiators of the first part in adjacency pairs. This research used quantitative descriptive research. The object of this research was one video contained (5 parts), the topic "all about language" with a video duration of 1 hour taken from the 'Six Minutes English Program on BBC Learning English’. The researcher collected and analyzed the data by applying the theory of Murata (1994). The conversation in the English Conversation video was used for data collection. The data were exported to the data sheet for identifying the types of adjacency pairs contained in the video. The result of the research showed 9 types of adjacency pairs on the Six Minutes English Program in BBC learning English in Youtube Channel. The types of adjacency pairs were Greeting-Greeting, Question-Answer, Request-Acceptance/Refusal, Blam-Admission/Denial, Assesment-Agreement/Disagreement, Command-Compliance/Incompliance, Suggestion-Acceptance/Refusal, Assertion-Agreement/Disagreement, Announcement-Acknowledgement. First, researcher found the most frequently appeared in adjacency pairs question-answer and assessment-agreement/disagreement. Also, researcher found the most frequently initiators of the first part in adjacency pairs namely the first participant. In conclusion, from the research video in 13 adjacency pairs, only 9 adjacency pairs often appear, 3 of which are not in the conversation between two participants. For further researchers, it is recomended to develop more about adjacency pairs and use other video conversations that contain many types of adjacency pairs.